The interaction between mental resilience and insomnia disorder on negative emotions in nurses in Guangdong Province, China - Zhan, Ningjing; Xu, Yixuan; Pu, Jiangfeng; Wang, Waner; Xie, Zhanghao; Huang, Huigen (Frontiers in Psychiatry, 2024)
Objective To investigate the current status of psychological resilience, insomnia and negative emotions among nurses in Guangdong Province, China. And to explore the effects of the interaction between psychological resilience and insomnia on negative emotions. Methods A cross-sectional survey method was used to select 1874 nurses in Guangdong Province from February 2023 to April 2023 for the survey. The Chinese version of the Psychological Resilience Scale (PRS), Insomnia Severity Index (ISI), Depression Anxiety and Stress Scale-21(DASS-21)were used in this study. We use SPSS 26.0 for statistical analysis. A simple effect analysis was established to analyze the association between psychological resilience, insomnia and negative emotions by using psychological resilience, insomnia and the interaction term. Results The overall PRS and ISI scores were (59.79 ± 17.29) and (9.83 ± 5.97). The scores of DASS-21 each dimension were (8.19 ± 9.02) for depression emotion,(7.93 ± 7.66) for anxiety emotion and (10.58 ± 9.77) for stress emotion. The results of the interaction effect analysis indicated that psychological resilience and insomnia exhibited statistically significant differences in the between-subjects effect test for depression emotion (r2 = 0.136, P<0.01), anxiety emotion (r2 = 0.127, P<0.01), and stress emotion (r2 = 0.142, P<0.01). Conclusion The nurses exhibited moderate levels of psychological resilience. Most of them have varying degrees of insomnia, with majority being classified as mild insomnia. Additionally, they demonstrated varying degrees of negative emotions. There was a negative correlation between psychological resilience and insomnia. Psychological resilience was negatively correlated with depression, anxiety and stress emotions. Insomnia was positively correlated with depression, anxiety and stress emotions. Furthermore, the interaction between psychological resilience and insomnia had an effect on all three dimensions of negative emotions. Consequently, hospital administrators may implement efficacious intervention strategies such as cognitive behavioral therapy and improving workplace climate in a timely manner according to the different psychological tolerance and severity of insomnia of nurses in order to reduce the occurrence of negative emotions among nurses and improve their mental health.